Realization of the Right to Health Protection in Insurance Medicine: The First Experience of Covid-19 - Lutsyuk, Pavlo; Bolokan, Inna; Davydova, Iryna; Chanysheva, Alina; Yakymchuk, Svitlana (Universidad Hemisferios, 2020)
This article analyze the effectiveness of insurance medicine and the negative consequences of its work, which we could observe in the first period of the pandemic. The research methodology is based on general and special scientific methods, in particular: formal-legal, historical-legal, comparative analysis, and modeling. The procedure and issues to be considered are as follows: in the introduction, we will consider the concept of